Exploring salivary microbiota in AIDS patients with different periodontal statuses using 454 GS-FLX Titanium pyrosequencing - Zhang, Fang; He, Shenghua; Jin, Jieqi; Dong, Guangyan; Wu, Hongkun (Frontiers in Cellular and Infection Microbiology, 2015)
Patients with acquired immunodeficiency syndrome (AIDS) are at high risk of opportunistic infections. Oral manifestations have been associated with the level of immunosuppression, these include periodontal diseases, and understanding the microbial populations in the oral cavity is crucial for clinical management. The aim of this study was to examine the salivary bacterial diversity in patients newly admitted to the AIDS ward of the Public Health Clinical Center (China). Saliva samples were collected from fifteen patients with AIDS who were randomly recruited between December 2013 and March 2014. Extracted DNA was used as template to amplify bacterial 16S rRNA. Sequencing of the amplicon library was performed using a 454 GS-FLX Titanium sequencing platform. Reads were optimized and clustered into operational taxonomic units for further analysis. A total of 10 bacterial phyla (106 genera) were detected. Firmicutes, Bacteroidetes and Proteobacteria were preponderant in the salivary microbiota in AIDS patients. The pathogen, Capnocytophaga sp., and others not considered pathogenic such as Neisseria elongata, Streptococcus mitis and Mycoplasma salivarium but which may be opportunistic infective agents were detected. Dialister pneumosintes, Eubacterium infirmum, Rothia mucilaginosa and Treponema parvum were preponderant in AIDS patients with periodontitis. Patients with necrotic periodontitis had a distinct salivary bacterial profile from those with chronic periodontitis. This is the first study using advanced sequencing techniques focused on hospitalized AIDS patients showing the diversity of their salivary microbiota.